2007
DOI: 10.1128/aem.01742-06
|View full text |Cite
|
Sign up to set email alerts
|

Rectoanal Junction Colonization of Feedlot Cattle by Escherichia coli O157:H7 and Its Association with Supershedders and Excretion Dynamics

Abstract: Feedlot cattle were observed for fecal excretion of and rectoanal junction (RAJ) colonization with Escherichia coli O157:H7 to identify potential "supershedders." RAJ colonization and fecal excretion prevalences were correlated, and E. coli O157:H7 prevalences and counts were significantly greater for RAJ samples. Based on a comparison of RAJ and fecal ratios of E. coli O157:H7/E. coli counts, the RAJ appears to be preferentially colonized by the O157:H7 serotype. Five supershedders were identified based on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 23 publications
4
123
5
1
Order By: Relevance
“…Although studies to date have not assessed aEPEC prevalence, other studies of stx and O157:H7 dairy prevalence have shown both higher (72·7%, 11·1-32·3%) [15,18] and lower (1%) levels [10]. Importantly, high-shedding cattle have been hypothesized to influence herd EHEC propagation, and only one was observed in the current study [21,22]. To date, this is the first assessment of EHEC prevalence on dairies in the Rocky Mountain biome, so it is possible that lower shedding prevalence and measured outcomes may be inherent to the particular environment studied.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although studies to date have not assessed aEPEC prevalence, other studies of stx and O157:H7 dairy prevalence have shown both higher (72·7%, 11·1-32·3%) [15,18] and lower (1%) levels [10]. Importantly, high-shedding cattle have been hypothesized to influence herd EHEC propagation, and only one was observed in the current study [21,22]. To date, this is the first assessment of EHEC prevalence on dairies in the Rocky Mountain biome, so it is possible that lower shedding prevalence and measured outcomes may be inherent to the particular environment studied.…”
Section: Discussioncontrasting
confidence: 54%
“…Importantly, those animals shedding high quantities of the pathogen ('high-shedders'; >10 3 -10 4 c.f.u./g faeces) may account for the majority of O157 contamination within a herd, increasing animal-to-animal transmission and risk of food chain contamination [18,21,22]. When classifying cows based on O157 shedding magnitude vs. positive shedding alone, outcomes for risk factor analyses can become altered [17].…”
Section: Introductionmentioning
confidence: 99%
“…38,39 These initial studies centered on bovine ruminal phages, but more recent O157:H7 phage research has moved to the recto-anal junction, the demonstrated major site of colonization in cattle. 15,40 Much less is known about O157:H7 colonization in sheep but the data suggests that it attaches more widely, including in the colon and rectum. [41][42][43] During our studies we found that half of the members of a single sheep flock carried the same new O157:H7-infecting phage, CEV2.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Scotland showed that cattle feces can contain from 100 to over 10 6 CFU of STEC O157:H7 per gram of feces (213). Increased shedding was associated with STEC mucosal colonization at the rectoanal junction (213,214). High-level shedding has implications for within-herd and between-farm transmission, as well as direct-contact and potential environmental exposure of humans, and has been discussed in more detail by Chase-Topping et al (215).…”
Section: Epidemiologymentioning
confidence: 99%